HOW HUMAN RESOURCE AGILITY CREATES SUSTAINABLE COMPETITIVE ADVANTAGE: THE MEDIATING EFFECT OF SERVICE INNOVATION - Darsana, I Made; Sudjana, I Made (LPPM Universitas Jambi, 2026)
The rapid advancement of digital transformation, artificial intelligence, and evolving customer expectations has reshaped the hospitality industry, requiring organizations to develop agile human resources and innovative service capabilities to maintain sustainable competitiveness. Despite growing interest in organizational agility and innovation, limited studies have integrated Human Resource Agility (HRA), Service Innovation (SI), and Sustainable Competitive Advantage (SCA) within the hospitality sector, particularly in emerging economies such as Indonesia. This study examines the effect of HRA on SCA and investigates the mediating role of SI. A quantitative explanatory approach was employed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). Data were collected through structured questionnaires from 300 employees and managers working in hotels, resorts, villas, and hospitality platforms across Bali, Jakarta, Yogyakarta, Bandung, and Surabaya. Reliability and validity assessments were conducted, followed by structural model evaluation using path coefficients, R², Q², f², and bootstrapping with 5,000 resamples. The results reveal that HRA positively and significantly influences both SI and SCA. SI also has a significant positive effect on SCA and partially mediates the relationship between HRA and SCA. These findings indicate that agile human resources enhance organizational adaptability and innovation capability, thereby strengthening long-term competitive advantage. The model demonstrates satisfactory explanatory and predictive power, supporting the Resource-Based View and Dynamic Capability Theory. The study’s novelty lies in integrating HRA, SI, and SCA within the Indonesian hospitality, contributing to the understanding of agility-driven innovation mechanisms. Practically, the findings importance of strengthening digital competencies, adaptive learning, and innovation-oriented organizational cultures to achieve sustainable competitiveness.